Emerging Asia: challenges for India and Singapore - Vohra, N. N. (New Delhi India International Centre & Manohar, 2003)
Contributed articles presented at the 2nd India-Singapore Colloquium held at New Delhi jointly organized by India International Centre and National University of Singapore.
Includes bibliographical references.
Keywords: India -- Foreign economic relations -- Singapore -- Congresses; Singapore -- Foreign economic relations -- India -- Congresses